The Role Of Women In Improving The Income For Economic Changes In Underprivileged Families - Wildan Suharso; Rina Karyati; Vivi Andriyani; Taufan Reza Achmadi; Hardianto Wibowo (Universitas Muhammadiyah Malang, 2020)
Women are a significant part of every aspect of life, from a large environment to the smallest one, women are sometimes appointed as heads of a unit or organization. The role of women is increasingly felt when in a family that has a category of poverty families, the ability of women to obtain a budget, and expenditure becomes very important. Economic change is faster if women can manage income, expenses, and households well. This study analyzes the role of women in increasing income for changes in the underprivileged economy using Participatory Rural Appraisal (PRA) by combining secondary data review and direct observation. Strengths Weaknesses Opportunities Threats (SWOT) Analysis is used to determine the environmental conditions used by case studies when conducting research. Analysis is used to determine the relationship between income and changes in the economic level. The data used are secondary data supported by direct data collection and field collection. The number of respondents used as sample data is 145 underprivileged families in the Lawang District of Malang, which are spread across four research areas with 36 data details in zone 1, 25 data in zone 2, 21 data in zone 3, and 63 data in zone 4. Research Results show that the role of women is very important in efforts to improve the welfare of underprivileged families and analysis of the participation of changes in the relationship between increasing income with changes in the economic level of underprivileged families.